Organizational Climate for Technology Capability Building in Small Firms. - Singh, Rajwinder (My University, 2007)
The advent of liberalization and globalization has brought forth profound economic, social, environmental and technological pressures on the organizations. The fierce competition situation arising because of globalization and liberation is forcing the organizations across the globe to realize that their survival is not feasible in the absence of R&D and innovation practices. If developing countries are to compete effectively in the world market, they must make every effort to develop new technologies. The objective of the present work is to analyze the technology development capabilities of small scale manufacturing industry especially the cutting tool and machine tool industry in the state of Punjab. The issues explored include, present status and future scope of R&D capabilities of small scale manufacturing industry regarding infrastructure facilities, support from government and academic institutes, reasons for low performance in the area of technology development etc. The present research work is divided into three phases. The first phase consists of extensive literature survey to determine the essential elements of a technology development programme. These include manpower, infrastructure facilities, government and interaction with external agencies. The first phase also reviews the conditions that encourage creativity culture at the firm level. The second phase presents a detailed survey conducted in cutting and machine tool small scale manufacturing units in the northern region of India. The survey explores the present status of R&D capabilities of this class of industry with regards to R&D policies, infrastructural facilities, investments in R&D, organization for R&D, support from government and academic institutes etc. and the reasons for the low performance of small scale sector in the area of technological innovations. The final phase comprises of a case study. The general objective of building this case study is to prove that employee behavior has a significant relationship with culture employed in the organization. The work has been carried out at “N.S. Enterprises, Panchkula”. The study has used the analysis of variance (ANOVA) technique in an attempt to prove that employee behavior is significantly related to organizational climate.
Keywords: Technology Development Capabilities; Fostering Creativity; Creativity Culture